Quantity of water-yield from space-Sungai Pahang watershed - Nurul Izzah, Abdul Rahman (2014)
Water-yield information is vital for water resources sustainability planning and security monitoring. Over the years, flow-rate gauges have been used to determine the flow of water as water-yield information from watershed, the result of hydrometeorology variability and human activity. The issue is flow-rate gauge information hard to obtain, especially during flood season. The main objective was to quantify water-yield information using simple hydrology cycle relationship, through fully satellite-based data sources as input at Sungai Pahang watershed. The specific objectives of the study were as follow; to establish database of satellite-based rainfall and actual evapotranspiration map, and to quantify water-yield using simple hydrology cycle relationship. Tropical Rainfall Measuring Mission Multi-satellite Precipitation Analysis (TMPA) and Moderate Resolution Imaging Spectro -radiometer (MODIS) bio-physical index satellite data were downloading from public domain resources to produced rainfall and actual evapotranspiration map, respectively. Both maps were used as input in hydrology cycle relationship to quantify water-yield information of study area. The results show that, satellite-based water-yield able to shows changes based on season. Therefore, satellitebased water-yield could be able as an alternative source of watershed water-yield. In the future, to get reliable results, it is necessary for those data to be validated.